Down-regulation of the hexose transport system: metabolic basis studied with a fibroblast mutant lacking phosphoglucose isomerase. - Ullrey, D B (1982)
Down-regulation ("curb") of hexose transport in Chinese hamster lung fibroblasts has been studied in a metabolic mutant highly defective in phosphoglucose isomerase (PGI; glucosephosphate isomerase; D-glucose-6-phosphate ketol-isomerase, EC 5.3.1.9). In the parental strain (PGI+) glucose as well as glucosamine and mannose were able to elicit a curb of the hexose transport system. In the PGI mutant, only glucose was able to mediate a transport curb. The inability of glucosamine and mannose to promote a transport curb in the PGI strain must be ascribed to the fact that the 6-esters of these aldohexoses are converted by their own specific deaminase and isomerase to fructose 6-phosphate, which initiates the pyruvate-tricarboxylate energy-yielding pathway but cannot be converted to glucose 6-phosphate in the mutant. The latter ester can be metabolized, but its metabolism in the mutant is confined to the pentose shunt. It is shown that inhibitors such as 2,4-dinitrophenol and malonate exert only slight inhibition of the pentose shunt yet release the glucose-mediated curb elicited by glucose and glucosamine in the parental PGI+ strain and also the glucose transport curb persisting in the PGI mutant.